ANALISA PERFORMANSI QUERY PADA DATABASE SMELL - Juanda Hakim Lubis (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2017)
Database Refactoring is a process to improve design of a database schema by observing some factors called database smells. Design changes of a database schema will affect processing time and cost for processing the query itself. Using a logic representation, which is entity relationship diagram (ERD), a design is made from a database schema that has been refactored. In compeleting query processing on a choosen bussines process, refactored schema can done all the query processing although if compared to schema without Refactoring from query processing point of view, the result is not far difference. But proven that there is some case where the cost for query processing can be reduced using refactored schema.